A Rare Case of 18-year-old female with Primary Sclerosing Cholangitis, Mixed Connective Tissue Disease, Short Stature - Fransisca Yustika Dewi Siahaan; Hery Djagat Purnomo; Khristophorus Heri Nugroho Hario Seno; Rakhma Yanti Hellmi (Faculty of Medicine, Diponegoro University, 2020)
Background: Primary sclerosing cholangitis (PSC) is a rare chronic immune-mediated liver disease affecting intra and extrahepatic bile ducts, in which inflammation and fibrosis are the main factors that lead to biliary stricture. The pathogenesis of this disease is still unclear. It happens approximately 0.5 to 1.3 cases per 100,000 person-years in Northern Europe. PSC is difficult to diagnose until complications arise. PSC can also be a manifestation of mixed connective tissue disease (MCTD) in the liver. A chronic immune disease that has occurred since childhood may result in delayed development and short stature. Case Presentation: A 18-year-old female presented with icteric, anemia, short stature, and absence of menstruation. Laboratory and radiological findings suggested obstruction of intra and extrahepatic biliary duct (conjugated bilirubin 11,80 mg/dL), severe anemia, normal sex hormone levels, increased RNP/SM antibodies. Histopathology showed liver cirrhosis suggestive for primary sclerosing cholangitis. The patient then was given biliary stenting, transfusion of packed red cell, immunosuppresive, corticosteroid, ursodeoxycholic acid. Within a year of treatment, there was a significant decrease of direct bilirubin and improvement in symptoms.Conclusion: Patient with PSC, MCTD, and short stature is a very rare case. This is the first case that has been found in dr. Kariadi Hospital, Semarang. It has high mortality rate and difficult to diagnose and treat. According to multiple guidelines, this patient should have liver transplantation , but in this case, biliary stenting and oral treatments have resulted in an excellent outcome.